Herstellung dünner Folien aus Lithium-Lanthan-Titanat zur Anwendung als Festkörperelektrolyt - Schröckert, Felix (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
In this work the production of a thin film of lithium lanthanum titanate by tape casting for use in a lithium ion solid state battery is described. The influence of the composition of the slip on its flow properties is investigated. The layers produced are characterized both individually and in connection with a composite anode made of lithium titanate. Their suitability for use in a solid-state battery is demonstrated.